Mitigating Vertical Handover Prediction in 4G Wireless Networks - Miyim, A.M; Ismail, Mahamod; Nordin, Rosdiadee; Taha, M (Journal of Asian Scientific Research, 2012)
The Provision of full mobility and good quality of service (QoS) are some of the key challenging tasks in mobile wireless networking. Interoperability between multiple access technologies (VHO) should be able to realize the vision of 4G technology and beyond that will allow mobile user equipment (UE) to roam freely when intersecting the cell-boundaries of different network platforms without losing the service. However, handover prediction seen as the method of determining the best network a mobile user should connect to, tend to prove difficult. This paper, therefore proposes a technique for predicting signal quality between the UE and base stations in two different (WiMAX and LTE-A) networks. The technique proposed makes use of two different thresholds to select the target base station with the strongest signal strength. Results from the proposed technique show that great improvement in network prediction was achieved.